Analisis docking tanaman meniran (Phyllanthus niruri L.) terhadap penghambatan asetilkolinesterase penyakit alzheimer - Silalahi , Ali Affan; Shufyani , Fahma; Siregar , Syati Manaharawan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Meniran plants (Phyllanthus niruri L.) are plants of the Phyllanthus genus. It is known that Phyllanthus genus plants contain astragaline, phyllanthine, hypopyllanthin compounds. Which is a flavonoid derivative that can function as an inhibitor of acetylcholinesterase enzyme against Alzheimer's disease. Based on the results of molecular docking, astragaline compounds have the best binding affinity compared to other compounds, namely -8.4 kcal/mol while the nativ ligand is -5.8 or in other words astragaline compounds derived from meniran plants (Phyllanthus niruri L.) can react when the drug binds to the target receptor in Alzheimer's disease. This type of research aims to determine the potential of compounds from the meniran plant (Phylanthus niruri L.) by inhibiting acetylcholinesterase in Alzheimer's disease. This study used molecular docking method with autodock vina program and visualized with discovery studio program. The conclusion of the study can be seen from the results of docking visualization which shows the form of hydrogen conventional that dominates the hydropobic bond. The interaction that occurs on the active side of the protein indicates that the compound has the ability. In other words, the compound can react as a drug when it binds to the target receptor in Alzheimer's disease.